(untitled) - Fellowes, Jessica (Thorndike, Maine, 2017)
"Set amid the legendary Mitford household in 1920s England and based on a real unsolved murder, a maid and one of the Mitford daughters find themselves entangled in the crimes of a murderer"--
Keywords: Nannies; Fiction; Murder; Fiction; Investigation; Large type books; Mystery fiction